Optimization of movable irrigation system and performance assessment of distribution uniformity under varying conditions - Shouqi, Yuan; Darko, Ransford Opoku; Xingye, Zhu; Junping, Liu; Kun, Tian (International Journal of Agricultural and Biological Engineering, 2017)
The evaluation of the performance of distribution uniformity by linearly moved irrigation system (LMIS) should consider the impacts of non uniformity of the water on crop yield. With increasing pressures to improve water use efficiency, plant productivity and farm profitability, questions continue to be raised concerning the future direction of irrigated agriculture. This study therefore aimed at evaluating water distribution under LMIS newly designed by the National Research Centre of Fluid Machinery Engineering and Technology, Jiangsu University, China. This article reports the real distribution of irrigation water under the LMIS with respect to sprinkler height above the ground surface as well as the consequence of different operating pressures. Water distribution coefficients used in the performance assessment were Christiansen’s coefficient of uniformity (CU), distribution uniformity (DU), scheduling coefficients (Sc) and the coefficient of variation (CV). The results showed that the mean CU ranged from 82.30% to 93.17%, and mean DU ranged from 70.39% to 88.44%. Also Sc values ranged from 1.13 to 1.42 with CV values ranging from 10.3% to 22.5%. The optimum method and results in this study can provide a reference to the operations for saving water and cost in the application of LMIS. Keywords: movable irrigation system, sprinkler irrigation, distribution uniformity, coefficient of uniformity, coefficient of variation, scheduling coefficient DOI: 10.3965/j.ijabe.20171001.2293 Citation: Yuan S Q, Darko R O, Zhu X Y, Liu J P, Tian K. Optimization of movable irrigation system and performance assessment of distribution uniformity under varying conditions. Int J Agric & Biol Eng, 2017; 10(1): 72–79.